(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Objectives: To determine the incidence of hypoparathyroidism in post-thyroid surgery patients operated in a tertiary care hospital Peshawar. Methods: This study was conducted from Oct 2021 to Sep 2022 at Irfan General Hospital Peshawar. Data was collected on questionnaires and uploaded on SPSS 25 after written consent. Patients on calcium supplements, autoimmune disease and history of neck radiations were excluded from the study. Parathyroid levels less than 10 pg/ml were defined as hypoparathyroidism. Results: Fifty-one patients were included in the study. Male gender was predominant i.e. 31. Mean age of the patients was 50.67 ±67 years. Mean serum parathyroid hormone level before surgery was 42.92 ±7.79pg/m. post-operatively, 12 patients had serum parathyroid hormone levels <10 pg/ml. At three months follow-up, only two patients had persistent low parathyroid levels. Low parathyroid hormone in these patients were observed more in female gender (p= 0.026). Patients with total thyroidectomy had a greater number of low parathyroid hormone levels post-operatively (p=0.06). Conclusion: Low parathyroid hormone levels in post-thyroid surgery patients are uncommon and resolves in most of the cases.